Adaptasi Teknologi Pada SMK Era Utama Di Desa Pancur Batu Melalui Pembuatan Website, Perancangan & Implementasi Infrastruktur Teknologi Informasi Serta Peningkatan Kompetensi Guru dengan Aplikasi Akuntansi dan Perpajakan - Dessyana, Dessyana; Br. Ginting, Suriani; Sembiring, Afen Prana Utama (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
This community service aims to develop and implement science and technology in line with technological developments. To improve teacher competence, this community service activity includes creating a school website, designing and implementing information technology infrastructure, and training in the use of the Accurate application and e-SPT tax. The steps of the activity begin with an analysis of the partner's problems, followed by offering and discussing solutions with the partner. The agreed solution is then compiled in the form of a mechanism, including website creation. This community service was carried out at SMK Era Utama, Pancurbatu, with training focused on teachers. The results of the activity showed that the designed website helped the school convey information to students effectively, as well as increasing the effectiveness of the learning process. In addition, the team also provided training in the latest accounting and taxation applications to SMK teachers to improve their competence. This training succeeded in encouraging an increase in the competence of teachers at SMK Era Utama.